1981
DOI: 10.1007/bf02088936
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent discipline: Different family members' perception

Abstract: Adolescence is perhaps the most difficult period of child rearing for parents. This study attempted to identify disciplinary techniques used by parents as perceived by mothers, fathers, and their adolescent children. Results indicated several significant areas of intrafamilial disagreement in regard to disciplinary techniques utilized, although all subjects tended to agree that some form of verbal reasoning was the primary disciplinary technique utilized with these adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

1984
1984
2000
2000

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…It was surprising that not one parent or stepparent variable was related to any of the wellbeing measures. However, such findings are consistent with other studies that have found differences in the perceptions of adolescents and their parents (e.g., Callan & Noller, 1986;McKenry, Price, & O'Bryant, 1981). Thus, our findings suggest the importance of adolescent perceptions in determining correlates of adolescent well-being.…”
Section: Discussionsupporting
confidence: 93%
“…It was surprising that not one parent or stepparent variable was related to any of the wellbeing measures. However, such findings are consistent with other studies that have found differences in the perceptions of adolescents and their parents (e.g., Callan & Noller, 1986;McKenry, Price, & O'Bryant, 1981). Thus, our findings suggest the importance of adolescent perceptions in determining correlates of adolescent well-being.…”
Section: Discussionsupporting
confidence: 93%
“…A nna Freud (1958) wrote '"that there are few situations in life more difficult to cope with than an adolescent son or daughter during their attempt to liberate themselves" (p. 278). Described as the most difficult stage of parenthood (e.g., Fisher & Fisher, 1976;McKenry, Price-Bonham, & O'Bryant, 1981;Pasley & Gecas, 1984), the adolescent period is associated with high levels of stress for family members (Aldous, 1978;Field & Widmayer, 1982) as well as increased marital discord (Gove & Peterson, 1980;Rapoport, Rapoport, & Strelitz, 1980). For the woman, whose identity is defined primarily through her relationships of intimacy and care (Gilligan, 1982), mothering the adolescent may entail an especially painful emotional struggle.…”
mentioning
confidence: 99%
“…And so many researchers are controlling for age and sex of child that it has finally become accepted practice in parenting research to make such distinctions. Many researchers have been especially interested in studying the differences in parentchild relationship by sex of both parent and child (Hendrickson, Perkins, White, and Buck, 1975;McKenry et al, 1981). Such studies have greatly enriched our understanding of dyadic relationships in families, and the impact of gender on the nature of such relationships.…”
Section: Stress/crisismentioning
confidence: 99%